INFLUÊNCIA DA APRENDIZAGEM ORGANIZACIONAL NA INOVAÇÃO DE PRODUTOS: ESTUDO EM EMPRESAS DE BASE TECNOLÓGICA DO VALE DA ELETRÔNICA, EM MINAS GERAIS - Rocha, Andréia de Fátima Ribeiro (2014)
This study investigates how organizational learning can influence innovation in products in technology-based companies. The companies studied are located in Local Productive Arrangement Electronics, informally known as the Electronic Valley, in the city of Santa Rita do Sapucaí, Minas Gerais. The theoretical framework involves the exploitation of main themes: organizational learning and innovation. The decision to study some companies located in this town is justified due to the fact this environment consists of a structure dedicated to the production of technological expertise with innovations. As specific objectives, this research seeks to identify shapes, fonts and the process of organizational learning that influenced the innovations presented by the companies. It is a qualitative, exploratory and descriptive research. The empirical data was collected through semi-structured interviews to owners and managers of companies. The result showed that shapes and internal and external sources of learning and the proximity of the academy as adjuvant in the development of innovations contributed and influenced the product innovation responsible for the increase of competitive advantage in business. This study also allowed point the relevance and contribution of organizational learning in product innovation and open paths to studies in other technology-based companies.